The culture of democracy a sociological approach to civil society - Xu, Bin (Hoboken, NJ, USA Polity Press, 2022)
"The Culture of Democracy provides the first systematic survey of the cultural sociology of civil society and offers a committed global perspective. It shows that, as everyone is eager to have their voice heard, cultural sociology can serve as an "art of listening," a thoroughly empirical approach that takes ideas, meanings, and opinions seriously, for people to contemplate significant theoretical and public issues." --Provided by publisher.
1. Introduction: The Culture of Democracy -- 2. Values, Codes, and Styles in the Public Sphere -- 3. Culture in Associational Life -- 4. Culture in Civic Engagement -- 5. The Culture of Democracy Under Undemocratic States -- 6. Global Civil Society -- 7. Cultural Sociology as an Art of Listening.
Includes bibliographical references and index.
Keywords: Civil society; Democracy